Effect of Probiotic and Population Density on the Growth Performance and Carcass Characteristics in Broiler Chickens - Vargas-Rodriguez, L.M.; Duran-Melendez, L.A; Garcia-Masias, J.A.; Arcos-Garcia, J.L.; Joaquin-Torres, B.M.; Ruelas-Inzunza, M.G. (International Journal of Poultry Science, 2013)
In order to assess the effect of a probiotic and population density on the growth performance and the carcass characteristics in broiler chickens, an experiment was conducted involving 208 1-day-old Peterson brand chicks. They were fed a corn and soy paste diet with 23 and 20 percent crude protein at the first and last stage respectively and 3.2 Mcal ME/kg. A completely randomized design with a 2 x 2 factorial arrangement, with two probiotics levels: 0 y 0.1% and two population density levels: 10 and 16 birds/m2, with four repetitions per treatment. The evaluation centered on growth performance: weight gain, feed consumption, food conversion and carcass variables: hot and chilled carcass weight, as well as breast, leg and thigh output. The growth performance was not affected (P>0.05) by probiotic and population density. The greatest yields (P